Forestry Borrow to Use Permit in Upstream Oil and Gas Activity: Ecology Governance, Development Administration, and Administration Law Perspective - Didik Sasono Setyadi; Deti Mulyati; Azeem Marhendra Amedi (Universitas Airlangga, 2021)
The “Forestry Borrow to Use (FBU) Permit” is an approval of the Ministry of Forestry to allow non-forestry activity to be conducted in Forestry Area. The Upstream Oil and Gas (OG) activity is commonly conducted in suburban or remote area where is located in such forestry area. In this kind of situation, a permission process must take place. So that there is a hierarchy: The Upstream OG activity Executor shall be in position as the Applicant, while the Ministry of Forestry shall be in the “higher” position as the Approver/Issuer the FBU Permit. This shows that between Governmental Institutions, one’s position is subordinate from another, thus causing a situation in which one institution’s plan can be disapproved by another government institution’s decision. Is this hierarchical structure conforming with the new values of coordination, synchronization and harmonization among government institution as required by Good Governance? This paper will analyze it in the perspective of Ecology Governance, Development Administration, Administrative Law in the Democratic Country